UniFlex - Collaborative on-line learning environment tool - Borch, Ole (Tidsskrift for Universiteternes Efter- og Videreuddannelse (UNEV), 2004)
Første gang publiceret i UNEV nr. 2: E-læringsplatforme - muligheder og potentialer, januar - marts 2004, red. Tom Nyvand og Michael Pedersen. ISSN 1603-5518. Increasing demands for remote on-line education are changing the way teaching and learning is performed. New behavior in using pedagogy and supporting technology is needed to drive the learning process. To facilitate the use of services for selected activities to participants in distance education, a web site named UniFlex (University Flexible learning) has been developed and brought into use. The site is a comprehensive set of bookmarks including course taking, upload/download, and - of special significance - collaborative on-line project work. UniFlex has been developed to meet the requirement for a simple and cheap personalized interactive site, supporting problem oriented and project organized study form, which has characterized Aalborg University for more than 27 years.